DEVELOPMENT TRENDS OF MODERN AUTOMATION SYSTEMS. (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the formation and development trends of modern automation systems in terms of the growth dynamics of the global industrial market in the 2020s and 2030s, technological transformation processes and the introduction of AI and IIoT solutions. On the basis of literature and international analytical reports, it is shown that the modernization of PLC/SCADA/DCS architectures, the share of smart sensors, industrial robots, cloud and edge platforms, as well as management algorithms based on artificial intelligence, as a result of which the Industrial Automation Market provides an average annual growth rate of 7-10 percent.